Hi, i've been posed a maths tutorial on functions and i'm just looking for someone to check my answer. I would get a classmate or lecturer to do it, but it's reading week and no-one is around.
So, With that in mind.
Given f(x)= 4x + 6 , g(x)= 2xSquared -3x + 5, and h(x)= 6x, find h(g(f(x)))
here's my answer
g(f(x))= 2(4x-6)squared -3(4x-6) + 5
-> 2(16x -36) -3(4x-6) + 5
-> (32x - 72) (12x-18) + 5
-> (44x - 90 + 5)
h(g(f(x))) = 6(44x - 90 + 5)
->(264x 540 + 30)
h(g(f(x)))= 264x -540 + 30
Did i mess up along the way or does this look right?
Any pointers you can give me would be good, as well as a way to display the character for squared, cubed etc. thanks in advance. Also apologies if i got this in the wrong forum.